Property Enhancement of Electrodeposited p-Cu₂O Thin Films via Hydrothermal Ethanol Etching for Solar Cell Applications Supporting the Sustainable Development Goals (SDGs) - Nurliyana Mohamad Arifin; Fariza Mohamad; Ming Wei Ping; Mohd Zamzuri Mohammad Zain; Masanobu Izaki (Bumi Publikasi Nusantara, 2026)
Electrodeposited p-Cu₂O thin films are promising absorber layers for sustainable solar cell applications, but their performance is limited by surface defects, high resistivity, and poor crystallinity. This study investigates hydrothermal ethanol etching as a post-deposition treatment to enhance p-Cu₂O thin films on FTO substrates. The treatment improved crystallinity, refined pyramidal morphology, increased visible-light absorption, reduced surface roughness, and lowered electrical resistivity. These enhancements are attributed to the removal of disordered surface regions and resistive secondary phases. The results indicate that controlled hydrothermal ethanol etching is an effective strategy for improving electrodeposited p-Cu₂O thin films for sustainable photovoltaic applications.